Common neural patterns of substance use disorder: a seed-based resting-state functional connectivity meta-analysis - Xiaonan Zhang; Haoyu Zhang; Yingbo Shao; Yang Li; Feifei Zhang; Hui Zhang (Translational Psychiatry)
Abstract Background Substance use disorder (SUD) shares common clinical features, including impulsive and compulsive behaviors, which are associated with dysfunctions in the brain’s reward circuit. Resting-state functional magnetic resonance imaging (rs-fMRI) studies have shown inconsistent results due to variability in the substances and stages of addiction. Identifying common neurobiological patterns in SUD could improve both our understanding of the disorder and the development of treatment strategies. Methods We conducted a comprehensive meta-analysis of 53 whole-brain rs-fMRI studies involving SUD patients. The Seed-based d Mapping toolkit was used to analyze connectivity patterns of key brain regions in the reward circuit: anterior cingulate cortex (ACC), prefrontal cortex (PFC), striatum, thalamus, and amygdala. Additionally, we explored correlations between resting-state functional connectivity (rsFC) patterns and impulsivity scores. Results The meta-analysis included 1700 SUD patients and 1792 healthy controls (HCs). Compared with HCs, SUD patients exhibited significant dysfunctions in the cortical-striatal-thalamic-cortical circuit. The ACC exhibited increased connectivity with the inferior frontal gyrus (IFG), lentiform nucleus, and putamen. The PFC demonstrated hyperconnectivity with the superior frontal gyrus (SFG) and striatum, as well as hypoconnectivity with the IFG. The striatum showed hyperconnectivity with the SFG and hypoconnectivity with the median cingulate gyrus (MCG). Thalamic connectivity with the SFG, dorsal ACC, and caudate nucleus was reduced. The amygdala exhibited hypoconnectivity with the SFG and ACC. Alterations in connectivity were also observed between several seed regions and the parahippocampal gyrus. Notably, the total score of the BIS-11 in SUD patients was significantly negatively correlated with reduced rsFC between the striatum and MCG. After family-wise error (FWE) correction, dysfunctions in the cortical-striatal-cortical circuit persisted. Conclusions Our findings revealed specific network abnormalities in SUD patients, highlighting disrupted connectivity within the brain’s reward circuit. These abnormalities were associated with impulsivity and may provide a theoretical basis for effective interventions to restore normal connectivity patterns.